Perencanaan Kesiapan Menghadapi Bencana Gempa sebagai Bagian Kebijakan Pelestarian Bahan Pustaka di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Hidayat, Rizki; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The purposes of this article are to describe: (1) the preparedness plan for facing earthquake in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat; (2) the problems that might be found in arranging the preparedness plan for facing earthquake in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat; (3) the efforts that can be taken to overcome the problems in arranging the preparedness plan for facing earthquake in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat. The data were collected by interviewing the officer of Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat and by conducting an observation. Based on this research, it can be concluded that: (1) the preparedness plan for facing earthquake in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat has not been properly implemented, particularly in its management; (2) the problems that might be found in arranging the preparedness plan for facing earthquake in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat are low understanding of the officer, lack of supporter element, and not yet considered elements of the preparedness plan for facing earthquake in arranging policies; (3) the efforts that can be taken to overcome the problems in arranging the preparedness plan for facing earthquake in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat are increasing the understanding of the officer, fulfilling the supporter element, and considering the supporter element of the preparedness plan for facing earthquake in arranging policies.Â Keywords: planning, preparedness, earthquakeÂ